Nilai-Nilai Pendidikan Karakter pada Ajaran Cinta dalam Tasawuf - Rahmi Damis (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
Students consider that teaching of love in tasawuf consists of great values of educational character. The teaching of love itself stimulates good character as manifested in the willingness to live in peace which in turn enable to guide one to exercise good speech and deeds that could make other people feel happy,sincere, fair, and honest.On the basis of this reliance, one should realize that love could only be reached by implementing systematic character education because started from purifying self from any sinful deeds and then followed by fulfilling self with good deeds, such as love, patience, and tolerance. The benefit that can be acquired from the concept of love are empathy as well as mutual help among people, harmonious and peaceful life as member of community as well as nation.